Ζ potential changing nanoparticles as cystic fibrosis transmembrane conductance regulator gene delivery system: an in vitro evaluation. (November 2017) - Prüfert, Felix; Bonengel, Sonja; Köllner, Saskia; Griesser, Janine; Wilcox, Matthew D; Chater, Peter I; Pearson, Jeffrey P; Bernkop-Schnürch, Andreas
Aim: Aim of the study was the development of ζ potential changing nanoparticles as gene delivery system for the cystic fibrosis transmembrane conductance regulator gene.Methods: Chitosan and carboxymethyl cellulose were modified with phosphotyrosine, a substrate for the brush border enzyme alkaline phosphatase. With these synthesized derivatives, different nanoparticle formulations, including the cystic fibrosis transmembrane conductance regulator gene were prepared by ionic gelation.Results: A change from negative to positive ζ potential after enzymatic cleavage could be observed. Transfection studies with HEK-293 and Caco-2 cells showed transfection rates comparable to Lipofectamine 2000. Transfection efficiencies were significantly decreased when phosphate cleavage and thus ζ potential change was inhibited by phosphatase inhibitor.Conclusion: The developed nanoparticles represent a promising gene delivery system.